ANALISIS TINGKAT KEUNTUNGAN USAHATANI BAWANG DAUN DI KELURAHAN MUARA SIBAN KECAMATAN DEMPO UTARA KOTA PAGAR ALAM - Ayumardensi, Rati; Ningrum, Puri Pratami Ardina (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2021)
This study aims to calculate how much profit and rate of profit on Allium fistulosum L farming in Muara Siban Village Dempo Utara Pagar Alam City. This research was carried out in Muara Siban Village Dempo Utara Pagar Alam City from April to June 2021. method The research used in this research is a survey method. The sampling method used in this study is the saturated sampling method (census). The data collection method used in this study is the method of observation, interviews and documentation which is asked directly to the respondents by using tools in the form of a list of questions that have been prepared in advance and data obtained from institutions related to this research. data processing and data analysis used in this study were coding, editing, and tabulating. Farming profits obtained by sample farmers in  Allium fistulosum L farming with an average cultivated area of 2 Ha, with an average income of Rp. 78,828,923/Lg/Mt, with an average production cost of Rp. 31.797.922/Lg/Mt, resulting in an average profit of Rp. 46.951.973/Lg/Mt. The profit level of leek farming obtained by the sample farmers in Muara Siban Village Dempo Utara Pagar Alam City with a cultivated area of 2 Ha, is 2.5, meaning that the costs incurred are Rp. 31.797.922 which will generate 2.5 times the revenue. carried out by farmers, examples are profitable for farmers and deserve to be continued.